Westerhus – Børnenes tænder - Alexandersen, Verner; Iregren, Elisabeth (Hikuin, 2000)
Westerhus. The dentitions of the children By Verner Alexandersen and Elisabeth Iregren In Westerhus on the island of Frösö in Jämtland the childhood was a stressful period with high mortality. In this study the living conditions of the children are discussed on the basis of the age distribution of infants, the prevalence of enamel hypoplasia and the tooth size of deciduous and permanent teeth. Gejvall’s age distribution of infants dying in the neonatal and the postneonatal periods was confirmed using both the atlas and the metric method of age assessment although the peak mortality in the age interval from 3-6 months was not as pronounced as suggested by Gejvall. The mortality in the postneonatal period is ascribed to infectious diseases and early supplement to breast-feeding with complementary foods. Various types of enamel hypoplasia were observed in deciduous teeth. Chronologically the hypoplasias occurred in the intrauterine, the neonatal and the postneonatal periods. Linear enamel hypoplasia in the permanent teeth was also noticed and related to malnutrition and systemic diseases after weaning. The prevalence was higher in the juvenile-adult age group than in the samples of children or mature individuals. Tooth size in the permanent dentition was reduced in comparison with samples of teeth from modern Nordic populations suggesting deficits in physical growth in early childhood. The sex dimorphism of the teeth was utilised to show that children buried North and South of the chapel tended to be distributed like the adult persons with the boys buried South of the chapel and the girls to the North of it. East of the chapel the children in mass graves belonged to both sexes.